2013
DOI: 10.1111/rda.12233
|View full text |Cite|
|
Sign up to set email alerts
|

Expression of Adrenergic Receptors in Bovine and Rabbit Oocytes and Preimplantation Embryos

Abstract: Catecholamines play an important role in embryogenesis, and data obtained in the rodent model indicate that they can act even during the preimplantation period of development. Using RT-PCR with specific oligonucleotide primers distinguishing among all members of the adrenergic receptor family, we examined expression of adrenergic receptors in bovine and rabbit oocytes, morulas and blastocysts. We found several profiles of adrenoceptor mRNA expression. Transcripts for some receptor subtypes (bovine alpha 2 rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 37 publications
(36 reference statements)
0
18
0
Order By: Relevance
“…Osthole, gramine, and hordenine act as human b2-AR agonists b2-AR expression in skeletal muscle has previously been confirmed in several species. In fact, mouse and human b2-ARs share 88% sequence homology (20). To make sure that these four food factors also act as human b2-AR agonists, luciferase assays were performed using a human b2-AR expression plasmid.…”
Section: Genementioning
confidence: 99%
“…Osthole, gramine, and hordenine act as human b2-AR agonists b2-AR expression in skeletal muscle has previously been confirmed in several species. In fact, mouse and human b2-ARs share 88% sequence homology (20). To make sure that these four food factors also act as human b2-AR agonists, luciferase assays were performed using a human b2-AR expression plasmid.…”
Section: Genementioning
confidence: 99%
“…There are data indicating that glucocorticoids and catecholamines may directly influence mammalian preimplantation embryos by binding to their respective receptors [ 5 , 6 , 7 ]. In addition, several animal studies have shown that glucocorticoid and catecholamine administration in vitro or in vivo can negatively affect developmental capacity and quality of preimplantation embryos [ 6 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
mentioning
confidence: 99%
“…If the fetus expresses vasopressin receptors (or adrenergic receptors in the case of epinephrine), this can also lead to physiologic changes in the fetus. No safe drug levels of vasopressin or epinephrine have been established in the first trimester and early second trimester, but animal embryos have been documented to express vasopressin receptors at as early as twelve conceptional days, and adrenergic receptors before implantation (Chen, Schreiber, and Brinton 2000; Čikoš et al 2013).…”
Section: Review Of the Literature And Ethical Considerations: Interstmentioning
confidence: 99%